2013
DOI: 10.4049/jimmunol.1300969
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Context-Dependent Role for E Boxes in the Targeting of Somatic Hypermutation

Abstract: Secondary B cell repertoire diversification occurs by somatic hypermutation (SHM) in germinal centers following antigen stimulation. In SHM, activation-induced cytidine deaminase (AID) mutates the variable region of the immunoglobulin (Ig) genes to increase the affinity of antibodies. Although somatic hypermutation (SHM) acts primarily at Ig loci, low levels of off-target mutation can result in oncogenic DNA damage, illustrating the importance of understanding SHM targeting mechanisms. A candidate targeting mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 41 publications
4
27
0
Order By: Relevance
“…Previous studies in mice using deletions of enhancers in Ig transgenes or at the endogenous Ig loci often had difficulty dissociating effects on SHM and transcription . Our previous approaches circumvented these issues by utilizing a knock‐in SHM reporter construct powered by a strong RSV promoter that masked the effect of test sequences on transcription . Our results suggested the possibility that different TF binding sites (and their accompanying TFs) mediated aspects of transcription enhancement and mutation enhancement to varying degrees.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Previous studies in mice using deletions of enhancers in Ig transgenes or at the endogenous Ig loci often had difficulty dissociating effects on SHM and transcription . Our previous approaches circumvented these issues by utilizing a knock‐in SHM reporter construct powered by a strong RSV promoter that masked the effect of test sequences on transcription . Our results suggested the possibility that different TF binding sites (and their accompanying TFs) mediated aspects of transcription enhancement and mutation enhancement to varying degrees.…”
Section: Discussionmentioning
confidence: 79%
“…The abundance of bHLH factors (Supporting Information Table 1A-D) was notable given the numerous studies implicating roles for E-boxes in SHM targeting [50,57,58]. E2A and TFAP4 were the most well-represented bHLH family members in the two Ramos extract conditions (Supporting Information Table 1A and B).…”
Section: Immobilized Template Analysis Linked To Mass Spectrometry Rementioning
confidence: 99%
“…Thus, this study clarified a long-standing controversy over the role of cis elements in targeting SHM [59]. Furthermore, novel cis -acting elements were identified in the Igl locus of the DT40 chicken B cell line that directly regulate AID-mediated sequence diversification [87-90]. In addition, it was shown that the E box motif CAGGTG in the context of Ig enhancers were sufficient and essential to target mutations to a nearby transcribed gene in transgenic DT40 cell lines [91].…”
Section: Cis Regulatory Elements In Shm Targetingmentioning
confidence: 92%
“…In addition, it was shown that the E box motif CAGGTG in the context of Ig enhancers were sufficient and essential to target mutations to a nearby transcribed gene in transgenic DT40 cell lines [91]. In this regard, it has been reported that the context sequences of E box motifs play a more important role in targeting SHM [87]. Overall, these studies highlight an important role of cis regulatory elements in AID targeting to Ig loci [77].…”
Section: Cis Regulatory Elements In Shm Targetingmentioning
confidence: 99%
“…In SHM, however, the transcribed V region does not form an R-loop, but generates an abundant single-stranded DNA structure [214,215]. Moreover, SHM is enhanced by the introduction of the transcription factor E2A-binding sequence CAGCTC (E-box motif), which may be prone to forming secondary non-B DNA structures, into the V region or the GFP gene [218][219][220]. Although these triplets are not consecutively arranged as a triplet track, their abundant clusters are frequent targets of mutation in the V region.…”
Section: Cleavage Target Sequence: Cis -Recognition and Transcriptionmentioning
confidence: 99%